The Cloaked Self. Professional de-cloaking and its implications for human engagement in nursing. - SHEERIN, FINTAN (My University, 2018)
PURPOSE: Much of our practice as nurses is predicated on the development of a trusting relationship between patient and nurse. Through this, the nurse and patient can identify the issues which are challenging health, the desired outcomes of care and the interventions that will be enacted, by both parties, in order to achieve these outcomes. Often, though, both nurses and patients find it difficult to put aside the relative roles that they play in health care and the level of engagement that is possible may not be achieved. METHODS: In this theoretical paper, I will explore the importance of human engagement to nursing practice, drawing, in a reflective and personal manner, on experiences gained throughout my 30 years of providing nursing service. CONCLUSIONS: Human engagement is central to the practice of nursing, but if engagement is to be valid, it must involve a dialogic transaction between the nurse and patient such that both parties are changed and there is a commitment to journey together, as humans, in the hope of finding positive outcomes for both. PRACTICE IMPLICATIONS: In a time of increasing tendency to build boundaries between people and communities, it is imperative that nursing does not lose its most essential quality: the coming together of human beings in dialogic engagement.
PUBLISHED
Keywords: Human engagement; Knowledge for practice; Nurse-patient/client relationship; Inclusive Society; Human Engagement; NURSING; NURSING CARE; Intellectual Disability; Health; Relationships